Modified polyphenyl plastic material and preparation method thereof

By adding a variety of modified ingredients to recycled polystyrene plastics, the problem of insufficient material performance is solved, and the toughness, strength, heat resistance and flame retardant properties of the material are significantly improved. It is suitable for high-end application fields, while achieving efficient recycling of resources and environmental protection.

CN119552458AActive Publication Date: 2025-03-04HUNAN ZHONGKE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510103633.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-04
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing recycled polyphenylene plastics have shortcomings in performance, especially in terms of toughness, strength, heat resistance and flame retardant properties, which are difficult to meet the requirements of high-end applications. At the same time, their wastes cause pollution to the environment and have low resource utilization.

Method used

Through innovative material component design and optimized preparation process, a modified regenerated polyphenylene plastic material was developed, and components such as hydrogenated SBS, PET-PBS, nanotitanium dioxide, antioxidants, calcium stearate, phosphobenzooxazine-containing prepolymers, graphene quantum dots, hyperbranched polyamide ester, rare earth complexes and organic montmorillonite were added to improve the comprehensive performance of the material.

Benefits of technology

It significantly improves the toughness, strength, heat resistance and flame retardant properties of the material, making it suitable for packaging, construction and other fields with high performance requirements, while reducing environmental pollution and improving the recycling rate of resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of environment-friendly materials, in particular to a modified regenerated polyphenyl plastic material and a preparation method thereof. The material is composed of a plurality of novel formula components such as regenerated polyphenyl plastic, hydrogenated SBS, PET-PBS, nano titanium dioxide, an antioxidant 1010, calcium stearate and a phosphorus-containing benzoxazine prepolymer. The preparation method comprises the following steps: synthesizing the novel component, pretreating the regenerated polyphenyl plastic, proportioning, mixing, and carrying out extrusion molding to obtain the product. Through a unique formula and a preparation process, the tensile strength, the impact strength, the thermal deformation temperature, the thermal stability, the flame retardance, the antibacterial property, the fluorescence property and the like of the modified regenerated polyphenyl plastic material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic material modification, and in particular to a modified polystyrene plastic material and a preparation method thereof. Background Art

[0002] In today's society, plastic products have been widely used in various fields due to their excellent performance and wide applicability. However, with the large-scale production and consumption of polystyrene plastic products, the amount of waste is also increasing day by day.

[0003] On the one hand, if a large amount of discarded polystyrene plastics are not properly handled, they will cause serious pollution to the environment. Polystyrene plastics are difficult to degrade in the natural environment, and their waste will remain in the soil for a long time, destroying the soil structure, affecting the air permeability and water penetration capacity of the soil, and then hindering the growth of plant roots and the absorption of nutrients, and having a negative impact on agricultural production and ecological balance. In the aquatic environment, discarded polystyrene plastics will float on the water surface or settle on the bottom of the water, which not only affects the beauty of the water body and the normal circulation of the ecosystem, but also seriously threatens the survival and reproduction of aquatic organisms and destroys the balance of the aquatic ecosystem. In addition, when discarded polystyrene plastics are incinerated, they will also release a large amount of harmful gases.

[0004] On the other hand, from the perspective of resource utilization, polystyrene plastics are made from valuable non-renewable resources such as petroleum, and large amounts of waste means a huge waste of resources. As global resources become increasingly scarce, it is essential to improve the recycling rate of resources. The emergence of recycled polystyrene plastics provides a way to solve this problem, but at present, recycled polystyrene plastics still have many shortcomings in terms of performance, which limits their further application and development.

[0005] Recycled polystyrene plastics often have the problem of insufficient toughness, which makes them easy to break when subjected to external impact. This is particularly evident in some application scenarios that require high material toughness, such as packaging materials need to withstand collisions during transportation, and building materials need to cope with certain external force deformation. Low strength is also a shortcoming of recycled polystyrene plastics. Its mechanical properties such as tensile strength and bending strength are difficult to meet the requirements of some high-end application fields, affecting the product's reliability and life. In addition, poor heat resistance makes recycled polystyrene plastics easy to deform and soften in high temperature environments, limiting its application under high temperature working conditions. For example, in some electronic and electrical equipment, plastic materials need to have certain heat resistance to ensure the normal operation of the equipment.

[0006] In summary, in order to reduce the pollution of waste polystyrene plastics to the environment, realize the effective recycling of resources, and meet the growing market demand for high-performance plastic materials, modifying recycled polystyrene plastics to improve their comprehensive performance has become a key issue to be solved in the field of plastic materials. Therefore, the present invention aims to develop a modified recycled polystyrene plastic material with superior performance through innovative material component design and optimized preparation process to overcome the defects of the prior art. Summary of the invention

[0007] The modified polyphenylene plastic material of the present invention is composed of the following materials in parts by weight: Basic ingredients: 80-100 parts of polystyrene plastic, as the matrix of the material, providing basic rigidity and molding properties for the product.

[0008] Reinforcement and toughening ingredients: 5-15 parts of hydrogenated styrene-butadiene-styrene block copolymer (SBS). Hydrogenated SBS has good flexibility and compatibility with polystyrene, and can form a dispersed phase in the material, effectively improving the toughness of the material. At the same time, its mutual entanglement with the molecular chain of polystyrene plastic helps to enhance the overall strength of the material. Polyethylene terephthalate-polybutylene succinate block copolymer (PET-PBS) 3-8 parts. PET-PBS has both the rigidity of PET and the flexibility of PBS, and can improve the toughness and processing performance of the material while increasing its strength. The ester bond in its molecular structure can interact with other components to enhance the interfacial bonding of the material.

[0009] .Functional additives: 0.5-3 parts of nano titanium dioxide. Nano titanium dioxide can not only improve the mechanical properties of the material, such as enhancing the strength and hardness of the material, but also has excellent ultraviolet shielding properties, which can effectively improve the weather resistance of the material and prevent the material from aging and degradation under ultraviolet radiation. In addition, its nano-size effect can improve the rheological and processing properties of the material, making it easier for the material to flow and form during processing.

[0010] Antioxidant 1010 0.5-2 parts. Antioxidant 1010 can effectively inhibit the oxidation reaction of materials during processing and use, and extend the service life of materials. During high-temperature processing, antioxidant 1010 can capture free radicals and prevent the oxidation chain reaction from proceeding, thereby protecting the molecular chain of the material from being destroyed.

[0011] 1-3 parts of calcium stearate. As a lubricant and stabilizer, calcium stearate can reduce the friction of the material during processing, allowing the material to flow more smoothly in the extruder and improve processing efficiency. At the same time, it can also interact with other ingredients in the material to enhance the stability of the material and prevent the performance of the material from deteriorating during storage and use.

[0012] . New formula components: 1-3 parts of phosphorus-containing benzoxazine prepolymer. Benzoxazine has excellent heat resistance, flame retardancy and mechanical properties. Phosphorus-containing benzoxazine prepolymer can form an expandable carbon layer at high temperature, which plays a role in heat insulation and oxygen isolation, and significantly improves the flame retardancy of the material. The active groups in its molecular structure can interact with the polystyrene plastic molecular chain, enhance the interfacial bonding force of the material, and thus improve the strength and toughness of the material. In addition, phosphorus-containing benzoxazine prepolymer can also improve the processing fluidity of the material to a certain extent, making it easier for the material to fill the mold during the molding process and improving product quality.

[0013] 0.1-0.5 parts of graphene quantum dots. Graphene quantum dots have excellent optical, electrical and mechanical properties. They can be evenly dispersed in the polystyrene plastic matrix to form a nano-scale reinforcement phase, significantly improving the mechanical properties of the material, such as tensile strength, bending strength and impact strength. At the same time, graphene quantum dots have good ultraviolet absorption ability, which can enhance the weather resistance of the material and prevent the material from aging and degradation under ultraviolet radiation. In addition, the introduction of graphene quantum dots can also improve the thermal conductivity of the material, help improve the heat dissipation capacity of the material, and is of great significance in the application of electronic equipment.

[0014] 2-5 parts of hyperbranched polyamide ester. Hyperbranched polyamide ester has a highly branched molecular structure, and contains a large number of active functional groups at the end of the molecular chain. These active functional groups can chemically react or physically entangle with components such as polystyrene plastics, hydrogenated SBS, PET-PBS, etc., enhance the compatibility between the components, and improve the comprehensive performance of the material. The branched structure of hyperbranched polyamide ester can also effectively prevent the expansion of cracks and improve the toughness of the material. In addition, it also has good film-forming properties, forming a protective film on the surface of the material to improve the chemical corrosion resistance of the material.

[0015] .Rare earth complexes 0.3-1 part. The rare earth complex can coordinate with the polystyrene plastic molecular chain, enhance the interaction between the molecular chains, and thus improve the strength and heat resistance of the material. At the same time, the presence of europium ions gives the complex excellent luminescent properties, which can give the material certain luminescent properties and expand the application field of the material, such as potential application value in decorative materials, anti-counterfeiting materials, etc. In addition, the rare earth complex also has certain antibacterial properties, which can inhibit the growth of microorganisms on the surface of the material and improve the hygienic properties of the material.

[0016] 1-4 parts of organic montmorillonite. Organic montmorillonite is a layered silicate mineral. After organic modification, its interlayer spacing increases, its surface properties are improved, and its compatibility with polymers is improved. In the polystyrene plastic system, organic montmorillonite can be evenly dispersed in the form of nano-scale flakes to form a "nano-composite effect", which significantly improves the strength, modulus and barrier properties of the material. The flake structure of organic montmorillonite can hinder the penetration of gas and liquid, and improve the water resistance and chemical corrosion resistance of the material. At the same time, it can also act as a nucleating agent, promote the crystallization of polystyrene plastics, and improve the thermal stability and dimensional stability of the material.

[0017] Further, the preparation method of the novel formula component is: Preparation of the phosphorus-containing benzoxazine prepolymer: bisphenol A, paraformaldehyde, and p-aminophenyl diphenyl phosphate are added to a three-necked flask in a molar ratio of 1:2:1, an appropriate amount of toluene is added as a solvent, and a small amount of p-toluenesulfonic acid is added as a catalyst. Under nitrogen protection, the temperature is raised to 110-120°C and stirred for reaction for 6-8 hours. During the reaction, bisphenol A, paraformaldehyde and p-aminophenyl diphenyl phosphate undergo a polycondensation reaction under the action of the catalyst to form a phosphorus-containing benzoxazine prepolymer. After the reaction is completed, the reaction solution is cooled to room temperature, poured into an excess of petroleum ether for precipitation, and the prepolymer is precipitated from the solution. After filtering, the obtained solid is washed with ethanol 3-4 times to remove residual solvents, catalysts and unreacted raw materials. Then vacuum dried at 60-70°C for 12-15 hours to obtain a pure phosphorus-containing benzoxazine prepolymer.

[0018] Preparation of the graphene quantum dots: Graphene quantum dots are prepared by a hydrothermal method. Graphite powder and potassium nitrate are added to concentrated sulfuric acid in a mass ratio of 1:5, and stirred for 30-40 minutes under ice bath conditions to fully disperse the graphite powder in the concentrated sulfuric acid. The mixed solution is then transferred to a reactor and reacted at 180-200°C for 12-18 hours. Under a high temperature and high pressure hydrothermal environment, the graphite powder is oxidized and peeled off to form graphene quantum dots. After the reaction is completed, it is naturally cooled to room temperature, the reaction product is diluted with deionized water, and then the unreacted impurities are removed by centrifugation. The supernatant is dialyzed for 48-72 hours to remove small molecule impurities, and finally freeze-dried to obtain graphene quantum dots.

[0019] .Preparation of the hyperbranched polyamide ester: trimethylolpropane, trimellitic anhydride and octadecylamine are used as raw materials and added into a three-necked flask with a stirrer, a thermometer and a reflux condenser in a molar ratio of 1:3:2. Under nitrogen protection, the temperature is raised to 180-200°C and the reaction is carried out for 4-6 hours. During the reaction, the progress of the reaction is monitored by measuring the acid value. When the acid value reaches the set value, it indicates that the reaction has reached the expected degree and the reaction is stopped. The reaction product is cooled to room temperature, dissolved with dichloromethane, and then poured into excess methanol for precipitation, so that the hyperbranched polyamide ester is precipitated from the solution. After filtering, the obtained solid is vacuum dried at 50-60°C for 8-10 hours to obtain a hyperbranched polyamide ester.

[0020] The rare earth complex Preparation: Weigh an appropriate amount of europium nitrate , o-phenanthroline (phen) and terephthalic acid All chemical reagents used were of analytical grade. Dissolve in anhydrous ethanol to prepare a solution with a concentration of 0.1-0.5 mol / L, and fully dissolve under magnetic stirring to obtain solution A. Dissolve o-phenanthroline (phen) in anhydrous ethanol to prepare a solution with a concentration of 0.2-0.6 mol / L to obtain solution B. Dissolve in anhydrous ethanol and prepare a solution with a concentration of 0.15-0.4 mol / L to obtain solution C. Slowly add solution B and solution C to solution A under stirring, control the dropping speed, allow the reaction to proceed at room temperature, and the dropping process lasts for about 30-60 minutes. After the dropwise addition is completed, heat the reaction system to 60-80°C, continue stirring the reaction for 4-8 hours, and allow the reaction to proceed fully. After the reaction is completed, cool the reaction mixture to room temperature, and then filter or centrifuge the reaction product to obtain a precipitate. Wash the precipitate several times with anhydrous ethanol to remove unreacted raw materials and by-products. Finally, dry the washed product in a vacuum oven, set the temperature to 60-80°C, and the drying time is 12-24 hours to obtain a pure rare earth complex. .

[0021] Preparation of the organic montmorillonite: sodium montmorillonite is added to deionized water to prepare a suspension with a mass fraction of 5-10%, and dispersed for 30-60 minutes under high-speed stirring to fully disperse the sodium montmorillonite in water. Then, an appropriate amount of hexadecyl trimethyl ammonium bromide is added, and the mass ratio of hexadecyl trimethyl ammonium bromide to montmorillonite is 1:2-1:3, and stirring is continued for 4-6 hours. Hexadecyl trimethyl ammonium bromide can be inserted into the interlayer of sodium montmorillonite, thereby increasing the interlayer spacing and improving the surface properties. After the reaction is completed, the suspension is centrifuged, and the obtained solid is washed with deionized water until there is no bromide ion in the washing liquid (tested with silver nitrate solution). Finally, the washed solid is dried at 80-100°C for 12-18 hours and ground to obtain the organic montmorillonite.

[0022] Further, the preparation method of the modified polystyrene plastic material: Raw material pretreatment: Polystyrene plastic is pretreated by combining physical screening and chemical cleaning to remove metal impurities and organic pollutants. Physical screening can remove larger metal particles and impurities through screening, magnetic separation and other methods, while chemical cleaning can use appropriate solvents or cleaning agents to remove organic pollutants. The treated polystyrene plastic is then crushed into particles with a particle size of less than 2mm for subsequent processing.

[0023] Preparation of new formula components: According to the above preparation method, phosphorus-containing benzoxazine prepolymer, graphene quantum dots, hyperbranched polyamide ester, and rare earth complex are synthesized respectively. and organic montmorillonite.

[0024] . Ingredients: Weigh hydrogenated SBS, PET-PBS copolymer, nano titanium dioxide, antioxidant 1010, calcium stearate, prepared phosphorus-containing benzoxazine prepolymer, graphene quantum dots, hyperbranched polyamide ester, rare earth complex according to the proportion. , organic montmorillonite, if a coupling agent is used, weigh the silane coupling agent KH550 at 0.5-2 times the mass of nano titanium dioxide.

[0025] Mixing: Add the pretreated polystyrene plastic particles and the above components into a high-speed mixer in turn, and stir at a speed of 800-1200r / min for 10-15 minutes to fully mix them. High-speed stirring can make the components disperse evenly in a short time to form a uniform mixture, laying a good foundation for subsequent extrusion molding.

[0026] Extrusion molding: Add the mixed materials into a twin-screw extruder, set the extruder temperature to 180-190℃ for the first section, 190-200℃ for the second section, and 200-220℃ for the third section, and the screw speed to 200-300r / min, and perform melt blending extrusion, cooling, air drying, pelletizing, homogenization, and packaging. During the extrusion process, the materials melt at high temperatures, and the components are further mixed and evenly mixed through the rotation and shear force of the screw, and physical and chemical changes occur to form a modified polystyrene plastic material with good performance. After cooling and air drying, the materials are pelletized for subsequent storage and transportation. The homogenization process can further ensure the stability of product quality, and finally packaging is performed.

[0027] Beneficial technical effects of the invention: The good compatibility of hydrogenated SBS with recycled polystyrene plastics enables it to be evenly dispersed in the matrix and effectively transfer stress, combined with the rigid segment reinforcement of PET-PBS and the nano-enhancement effect of graphene quantum dots. This means that when the material is subjected to external forces, it can better resist stretching and impact, reduce the risk of rupture, and can be widely used in packaging, construction and other fields that require high material strength and toughness. The europium ions in the rare earth complex have empty electron orbits and can form coordination bonds with the atoms or groups containing lone pairs of electrons on the polystyrene plastic molecular chain. The formation of this coordination bond is like building a bridge between the molecular chains, tightly connecting the originally relatively loose molecular chains together. When the material is heated, these additional coordination bonds require higher energy to be destroyed, so that the molecular chains will not slide or separate easily, thereby improving the thermal stability of the material, which is manifested as enhanced heat resistance of the material. In a high temperature environment, the metal-ligand bonds in its structure can remain stable within a certain temperature range and are not easy to break. When the material is locally heated, the rare earth complex can act as a thermal stability center to absorb and disperse heat, preventing the rapid transfer and accumulation of heat inside the material. This is like setting up multiple "heat dissipation points" inside the material to avoid material degradation caused by local overheating. The expanded carbon layer formed by the phosphorus-containing benzoxazine prepolymer at high temperature, and the coordination effect between the rare earth complex and the molecular chain, greatly enhance the heat resistance and thermal stability of the material. This enables the material to maintain stable performance under high temperature conditions, and is suitable for components of heating equipment such as electronic appliances, avoiding the normal operation of the equipment affected by thermal deformation. The present invention gives the material excellent flame retardant properties, effectively preventing the spread of flames, and significantly improves fire safety in applications in the fields of construction and electronics. Rare earth complexes also give the material antibacterial properties, which are suitable for scenes with strict hygiene requirements such as food packaging and medical devices. In addition, the unique fluorescent properties open up new application space for the material in the fields of decoration and anti-counterfeiting. The addition of calcium stearate and phosphorus-containing benzoxazine prepolymer improves the processing fluidity of the material, allowing it to be smoothly formed in the extruder. At the same time, the present invention uses waste polystyrene as raw material, realizes resource recycling and reuse, reduces environmental pollution, and has significant environmental benefits. DETAILED DESCRIPTION

[0028] Example 1 1. Preparation of phosphorus-containing benzoxazine prepolymer In a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, bisphenol A, paraformaldehyde and p-aminophenyl diphenyl phosphate are added in sequence, and the molar ratio is precisely controlled to be 1:2:1. Then, an appropriate amount of toluene is added to the flask as a solvent, and the amount of toluene is preferably sufficient to dissolve the reactants and is easy to stir. A small amount of p-toluenesulfonic acid is added as a catalyst, and its amount is about 0.5%-1% of the total mass of the reactants. Under nitrogen protection, the reaction system is slowly heated to 110-120°C and stirred in this temperature range for 6-8 hours. During the reaction, the changes in the reaction system are closely observed, and the progress of the reaction is monitored by thin layer chromatography (TLC). When TLC shows that the reactants are basically converted, stop heating and cool the reaction solution to room temperature. Subsequently, the reaction solution is poured into an excess of petroleum ether, and the phosphorus-containing benzoxazine prepolymer will precipitate. The precipitate is collected by filtration, and the resulting solid is washed 3-4 times with ethanol to remove residual toluene, p-toluenesulfonic acid and unreacted raw materials. Finally, the washed solid is placed in a vacuum drying oven and vacuum dried at 60-70° C. for 12-15 hours to obtain a pure phosphorus-containing benzoxazine prepolymer. The obtained phosphorus-containing benzoxazine prepolymer is characterized by infrared, and an absorption peak corresponding to the functional group appears at the characteristic peak, indicating that the synthesis is successful.

[0029] (II) Preparation of graphene quantum dots Graphene quantum dots were prepared by hydrothermal method. First, graphite powder and potassium nitrate were added to concentrated sulfuric acid in a mass ratio of 1:5, and stirred for 30-40 minutes with a strong stirrer under ice bath conditions to ensure that the graphite powder was fully dispersed in the concentrated sulfuric acid. Then, the mixed solution was transferred to a high-pressure reactor, the reactor was sealed and placed in an oven, and reacted at 180-200°C for 12-18 hours. After the reaction, the reactor was allowed to cool naturally to room temperature. Next, the reaction product was diluted with a large amount of deionized water at a dilution ratio of about 1:10, and centrifuged at a speed of 8000-10000r / min for 15-20 minutes by a high-speed centrifuge to remove unreacted impurities. The supernatant was placed in a dialysis bag and dialyzed in deionized water for 48-72 hours, during which the deionized water was replaced every 8-12 hours to fully remove small molecule impurities. Finally, the dialyzed solution was freeze-dried to obtain black powdered graphene quantum dots. Through transmission electron microscopy (TEM) observation, the particle size distribution of graphene quantum dots is between 5-10nm, proving that the preparation is successful.

[0030] (III) Preparation of hyperbranched polyamide In a three-necked flask with a stirrer, a thermometer and a reflux condenser, trimethylolpropane, trimellitic anhydride and octadecylamine are added in a molar ratio of 1:3:2. Under nitrogen protection, the reaction system is heated to 180-200°C and reacted for 4-6 hours. During the reaction, a small amount of sample is taken every hour, and the acid value is determined by acid-base titration to monitor the progress of the reaction. When the acid value reaches the set value (generally the acid value is reduced to 10%-15% of the initial acid value), the reaction is stopped. The reaction product is cooled to room temperature, dissolved with an appropriate amount of dichloromethane, and then slowly poured into excess methanol, and hyperbranched polyamide ester will precipitate. The precipitate is collected by filtration, and the obtained solid is vacuum dried in a vacuum drying oven at 50-60°C for 8-10 hours to obtain hyperbranched polyamide ester. The molecular weight is determined by gel permeation chromatography (GPC), and the molecular weight distribution is between 5000-10000, indicating that the polymerization reaction has achieved the expected effect.

[0031] (IV) Rare earth complexes Preparation Weigh an appropriate amount of europium nitrate , o-phenanthroline (phen) and terephthalic acid All chemical reagents used were of analytical grade. Dissolve in anhydrous ethanol to prepare solution A with a concentration of 0.1-0.5 mol / L. Stir thoroughly for 30-40 minutes under magnetic stirring to ensure that europium nitrate is completely dissolved. Dissolve o-phenanthroline (phen) in anhydrous ethanol to prepare solution B with a concentration of 0.2-0.6 mol / L. Stir until completely dissolved. Dissolve in anhydrous ethanol and prepare a solution C with a concentration of 0.15-0.4 mol / L. Under stirring, slowly add solution B and solution C to solution A, control the drop rate to 1-2 drops per second, allow the reaction to proceed at room temperature, and the drop process lasts for about 30-60 minutes. After the drop addition is completed, heat the reaction system to 60-80°C and continue stirring the reaction for 4-8 hours. After the reaction is completed, cool the reaction mixture to room temperature and then obtain a precipitate by filtration or centrifugation. Wash the precipitate 3-5 times with anhydrous ethanol to remove unreacted raw materials and by-products. Finally, dry the washed product in a vacuum oven at 60-80°C for 12-24 hours to obtain a pure rare earth complex. Its structure was characterized by single-crystal X-ray diffraction, confirming that its structure was consistent with expectations.

[0032] (V) Preparation of organic montmorillonite Sodium montmorillonite is added to deionized water to prepare a suspension with a mass fraction of 5-10%, and dispersed at a speed of 3000-5000r / min for 30-60 minutes using a high-speed stirrer. Then add an appropriate amount of hexadecyltrimethylammonium bromide, the mass ratio of which to montmorillonite is 1:2-1:3, and continue stirring for 4-6 hours. After the reaction is completed, the suspension is centrifuged at a speed of 5000-8000r / min for 15-20 minutes, and the obtained solid is washed with deionized water until there is no bromide ion in the washing liquid (tested with 0.1mol / L silver nitrate solution until no white precipitate is generated after adding the silver nitrate solution). Finally, the washed solid is dried at 80-100°C for 12-18 hours and ground to obtain organic montmorillonite. According to X-ray diffraction (XRD) analysis, the interlayer spacing of organic montmorillonite is significantly larger than that of sodium montmorillonite, indicating that the modification is successful.

[0033] Example 2 Material preparation: weigh 80 parts of polystyrene plastic, 5 parts of hydrogenated SBS, 3 parts of PET-PBS, 0.5 parts of nano-titanium dioxide, 0.5 parts of antioxidant 1010, 1 part of calcium stearate, 1 part of the above-prepared phosphorus-containing benzoxazine prepolymer, 0.1 parts of graphene quantum dots, 2 parts of hyperbranched polyamide ester, 0.3 parts of rare earth complex , 1 part of organic montmorillonite, 0.25 parts of silane coupling agent KH550 (based on the mass of nano titanium dioxide).

[0034] .Pre-treat the polystyrene plastic by using physical screening to remove larger impurity particles, then soak and clean it with an organic solvent (such as acetone) to remove organic pollutants, and then crush it into particles with a particle size of less than 2mm.

[0035] Weigh each component according to the above batching steps.

[0036] Add each component into a high-speed mixer in turn and stir at a speed of 1000 r / min for 12 minutes to fully mix them.

[0037] The mixed materials were added into a twin-screw extruder, the extruder temperature was set to 185°C for the first section, 195°C for the second section, 210°C for the third section, and the screw speed was 250 r / min for melt blending, extrusion, cooling, air drying, pelletizing, homogenization, and packaging.

[0038] Performance test: The prepared materials were tested for performance, with tensile strength of 50MPa, impact strength of 30kJ / ㎡, heat deformation temperature of 90℃, melt flow rate of 4.5g / 10min, initial decomposition temperature of 360℃ in TGA test, limiting oxygen index of 30%, antibacterial rate of 90%, and red fluorescence under ultraviolet light excitation.

[0039] Example 3 Material preparation: weigh 90 parts of polystyrene plastic, 10 parts of hydrogenated SBS, 5 parts of PET-PBS, 1.5 parts of nano-titanium dioxide, 1 part of antioxidant 1010, 2 parts of calcium stearate, 2 parts of the above-prepared phosphorus-containing benzoxazine prepolymer, 0.3 parts of graphene quantum dots, 3 parts of hyperbranched polyamide ester, 0.6 parts of rare earth complex , 2 parts of organic montmorillonite, 0.75 parts of silane coupling agent KH550.

[0040] Preparation process: The steps of preparing the new formula components, pretreating the polystyrene plastic and mixing the ingredients in Example 1 were repeated.

[0041] Add all components into a high-speed mixer and stir at a speed of 1100 r / min for 13 minutes.

[0042] The mixed material was added into a twin-screw extruder, the extruder temperature was set to 188°C in the first section, 198°C in the second section, 215°C in the third section, and the screw speed was 260 r / min, and melt blending extrusion, cooling, air drying, pelletizing, homogenization, and packaging were performed.

[0043] Performance test: tensile strength is 58MPa, impact strength is 38kJ / ㎡, heat deformation temperature is 95℃, melt flow rate is 4.2g / 10min, initial decomposition temperature is 375℃, limiting oxygen index is 32%, antibacterial rate reaches 95%, and fluorescence intensity is enhanced.

[0044] Example 4 Material preparation: weigh 100 parts of polystyrene plastic, 15 parts of hydrogenated SBS, 8 parts of PET-PBS, 3 parts of nano-titanium dioxide, 2 parts of antioxidant 1010, 3 parts of calcium stearate, 3 parts of the above-prepared phosphorus-containing benzoxazine prepolymer, 0.5 parts of graphene quantum dots, 5 parts of hyperbranched polyamide ester, 1 part of rare earth complex , 4 parts of organic montmorillonite, 1.5 parts of silane coupling agent KH550.

[0045] Preparation process: Same as the relevant steps of Example 1 and Example 2.

[0046] Add all components into a high-speed mixer and stir at a speed of 1200 r / min for 15 minutes.

[0047] The mixed material was added into a twin-screw extruder, the extruder temperature was set to 190°C in the first section, 200°C in the second section, 220°C in the third section, and the screw speed was 300 r / min, and melt blending extrusion, cooling, air drying, pelletizing, homogenization, and packaging were performed.

[0048] Performance test: tensile strength is 65MPa, impact strength is 45kJ / ㎡, heat deformation temperature is 100℃, melt flow rate is 3.8g / 10min, initial decomposition temperature is 385℃, limiting oxygen index is 35%, antibacterial rate reaches 98%, and the fluorescent effect is more significant.

[0049] 1. Comparative product introduction Unmodified polystyrene plastic: Common polystyrene plastic on the market that has not undergone any modification and is directly recycled from waste polystyrene. Its performance is greatly affected by the source of waste polystyrene and the recycling process. It generally has problems such as low tensile strength, poor impact toughness, and insufficient heat resistance. Generally, the tensile strength is 25-35MPa, the impact strength is 10-15kJ / ㎡, the heat deformation temperature is 60-70℃, and it has no obvious flame retardant, antibacterial and fluorescent properties.

[0050] Product A: Ordinary SBS is used as a toughening agent (the mass ratio of styrene to butadiene is 30:70, and the molecular weight is 150,000), and waste polystyrene is used as a raw material to prepare polystyrene plastic products. In addition to ordinary SBS and recycled polystyrene, 2 parts of stearic acid are added as a lubricant, 0.5 parts of antioxidant 168, and 0.3 parts of ultraviolet absorber UV-531. The tensile strength is 35MPa, the impact strength is 15kJ / ㎡, the heat deformation temperature is 70℃, the melt flow rate is 5.2g / 10min, the initial decomposition temperature is 320℃, the limiting oxygen index is 20%, the antibacterial rate is less than 50%, and there is no fluorescent performance.

[0051] Product B: Polystyrene plastic products are prepared using unmodified PET as a reinforcing agent (with a characteristic viscosity of 0.65 dL / g). In addition to unmodified PET and recycled polystyrene, 3 parts of calcium carbonate are added as a filler, 0.8 parts of zinc stearate as a lubricant, and 0.6 parts of antioxidant CA. The tensile strength is 40MPa, the impact strength is 20kJ / ㎡, the heat deformation temperature is 75℃, the melt flow rate is 4.9g / 10min, the initial decomposition temperature is 330℃, the limiting oxygen index is 22%, the antibacterial rate is less than 60%, and there is no fluorescent property.

[0052] Product C: Polystyrene plastic products are prepared using linear low-density polyethylene (LLDPE) as a modifier (density of 0.92g / cm³, melt flow rate of 2g / 10min). In addition to LLDPE and recycled polystyrene, 1.5 parts of talc powder are added as a filler, 0.5 parts of stearic acid amide as a lubricant, and 0.4 parts of antioxidant 1076. The tensile strength is 42MPa, the impact strength is 22kJ / ㎡, the heat deformation temperature is 80℃, the melt flow rate is 5.0g / 10min, the initial decomposition temperature is 340℃, the limiting oxygen index is 23%, the antibacterial rate is less than 65%, and there is no fluorescent property.

[0053] (II) Efficiency enhancement description Tensile strength: The tensile strength of unmodified polystyrene plastic is usually 25-35MPa, product A is 35MPa, product B is 40MPa, and product C is 42MPa. The tensile strength of Example 1 of the present invention is 50MPa, Example 2 is 58MPa, and Example 3 is 65MPa. This is because the hydrogenated SBS in the present invention has good compatibility with polystyrene plastic, and the molecular chains are entangled with each other to enhance the integrity of the material; the rigid segments of PET-PBS provide additional strength support; the graphene quantum dots are evenly dispersed in the matrix, playing a nano-enhancement role; the active functional groups of the hyperbranched polyamide ester interact with other components to enhance the interfacial bonding force; the nano-sheet structure of the organic montmorillonite also contributes positively to the improvement of tensile strength. The synergistic effect of various components is combined to greatly improve the tensile strength of the product of the present invention, which is 43%-100% higher than that of unmodified polystyrene plastic, 43%-86% higher than that of product A, 30%-63% higher than that of product B, and 24%-55% higher than that of product C.

[0054] Impact strength: The impact strength of unmodified polystyrene plastic is 10-15 kJ / ㎡, product A is 15 kJ / ㎡, product B is 20 kJ / ㎡, and product C is 22 kJ / ㎡. The impact strength of Example 1 of the present invention is 30 kJ / ㎡, Example 2 is 38 kJ / ㎡, and Example 3 is 45 kJ / ㎡. The elastomeric properties of hydrogenated SBS and the highly branched structure of hyperbranched polyamide ester can effectively disperse and absorb energy when the material is impacted, preventing the rapid expansion of cracks, thereby significantly improving the impact strength. Compared with unmodified polystyrene plastic, the impact strength of the product of the present invention is increased by 100%-200%, compared with product A, it is increased by 100%-200%, compared with product B, it is increased by 90%-125%, and compared with product C, it is increased by 82%-105%.

[0055] Heat deformation temperature: The heat deformation temperature of unmodified polystyrene plastic is 60-70°C, product A is 70°C, product B is 75°C, and product C is 80°C. The heat deformation temperature of Example 1 of the present invention is 90°C, Example 2 is 95°C, and Example 3 is 100°C. The expanded carbon layer formed by the phosphorus-containing benzoxazine prepolymer at high temperature can play a heat-insulating role, and the coordination effect of the rare earth complex and the polystyrene plastic molecular chain enhances the interaction force between molecules, making the material less likely to deform at high temperatures. Compared with unmodified polystyrene plastic, the heat deformation temperature of the product of the present invention is increased by 29%-43%, compared with product A, it is increased by 29%-43%, compared with product B, it is increased by 27%-33%, and compared with product C, it is increased by 20%-25%.

[0056] Thermal stability: The initial decomposition temperature was tested by TGA. The initial decomposition temperature of unmodified polystyrene plastic is relatively low, generally around 300°C, with product A at 320°C, product B at 330°C, and product C at 340°C. The initial decomposition temperature of Example 1 of the present invention is 360°C, Example 2 is 375°C, and Example 3 is 385°C. Antioxidant 1010 effectively inhibits the oxidative degradation of the material at high temperatures, and the presence of phosphorus-containing benzoxazine prepolymers and rare earth complexes enhances the thermal stability of the material. Compared with unmodified polystyrene plastic, the initial decomposition temperature of the product of the present invention is increased by 20%-28%, compared with product A, it is increased by 13%-20%, compared with product B, it is increased by 14%-17%, and compared with product C, it is increased by 13%-15%. This greatly expands the application scope of the modified polystyrene plastic of the present invention in high temperature environments. For example, in some industrial production environments that need to withstand a certain temperature or electronic product heat dissipation components, the product of the present invention can maintain more stable performance.

[0057] Flame retardant properties: The limiting oxygen index of unmodified polystyrene plastic is usually less than 20%, which is a flammable material. The limiting oxygen index of product A is 20%, product B is 22%, and product C is 23%. The limiting oxygen index of Example 1 of the present invention is 30%, Example 2 is 32%, and Example 3 is 35%. The expanded carbon layer formed by the decomposition of the phosphorus-containing benzoxazine prepolymer at high temperature can isolate oxygen and heat, effectively prevent the spread of flames, and significantly improve the flame retardant properties of the material. Compared with unmodified polystyrene plastic, the limiting oxygen index of the product of the present invention is increased by 50%-75%, compared with product A, it is increased by 50%-75%, compared with product B, it is increased by 45%-59%, and compared with product C, it is increased by 30%-52%. In fields such as construction and electronics that have high requirements for fire safety, the flame retardant performance advantage of the product of the present invention makes it a safer and more reliable material choice.

[0058] Antibacterial properties: Unmodified polystyrene plastics basically have no antibacterial properties. The antibacterial rate of product A is less than 50%, the antibacterial rate of product B is less than 60%, and the antibacterial rate of product C is less than 65%. The antibacterial rate of Example 1 of the present invention reaches 90%, Example 2 is 95%, and Example 3 is 98%. The europium ions in the rare earth complex have certain antibacterial activity and can inhibit the growth and reproduction of bacteria, so that the products of the present invention have obvious advantages in application scenarios with high hygiene requirements, such as food packaging, medical equipment and other fields. Compared with product A, the antibacterial rate of the product of the present invention has increased by 40-48 percentage points, compared with product B, it has increased by 35-38 percentage points, and compared with product C, it has increased by 33-33 percentage points.

[0059] Fluorescence performance: Unmodified polystyrene plastics and products A, B, and C have no fluorescence performance. , Example 1 can emit red fluorescence under ultraviolet light excitation, Example 2 has enhanced fluorescence intensity, and Example 3 has more significant fluorescence effect. This characteristic gives the material unique optical properties, making it have potential application value in the fields of decorative materials, anti-counterfeiting materials, etc., greatly expanding the application scope of polystyrene plastics, which is an advantage that existing unmodified and commonly modified polystyrene plastics do not have.

[0060] Melt flow rate and processing performance: The melt flow rate of unmodified polystyrene plastics fluctuates greatly due to the influence of raw materials and recycling processes, and is generally between 3-6g / 10min. The melt flow rate of product A is 5.2g / 10min, that of product B is 4.9g / 10min, and that of product C is 5.0g / 10min. The melt flow rate of Example 1 of the present invention is 4.5g / 10min, that of Example 2 is 4.2g / 10min, and that of Example 3 is 3.8g / 10min. Although the melt flow rate of the product of the present invention is slightly lower than that of some comparative products, in the actual processing process, the addition of phosphorus-containing benzoxazine prepolymer and calcium stearate makes the material have good fluidity in the extruder, and can smoothly complete the processing and molding processes such as injection molding and extrusion. Moreover, a lower melt flow rate means that the material is easier to maintain its shape during the molding process, reduces deformation and defects of the product, and improves the molding quality and dimensional accuracy of the product. For example, when injection molding plastic products of complex shapes, the product of the present invention can better fill the mold cavity and ensure the integrity and surface quality of the product.

Claims

1. A modified polystyrene plastic material, characterized in that: The invention is composed of the following materials in parts by weight: 80-100 parts of polystyrene plastic, 5-15 parts of hydrogenated styrene-butadiene-styrene block copolymer, 3-8 parts of polyethylene terephthalate-polybutylene succinate block copolymer, 0.5-3 parts of nano titanium dioxide, 0.5-2 parts of antioxidant 1010, 1-3 parts of calcium stearate, 1-3 parts of phosphorus-containing benzoxazine prepolymer, 0.1-0.5 parts of graphene quantum dots, 2-5 parts of hyperbranched polyamide ester, and rare earth complex. 0.3-1 parts, organic montmorillonite 1-4 parts.

2. The modified polystyrene plastic material according to claim 1, characterized in that: The hydrogenation degree of the hydrogenated styrene-butadiene-styrene block copolymer is greater than 90%, the mass ratio of styrene to butadiene is 30:70, and the molecular weight is 150,000.

3. The modified polystyrene plastic material according to claim 1, characterized in that: The molar ratio of polyethylene terephthalate to polybutylene succinate segments in the polyethylene terephthalate-polybutylene succinate block copolymer is 3:2, and the intrinsic viscosity is 0.75 dL / g.

4. The modified polystyrene plastic material according to claim 1, characterized in that: The nano titanium dioxide is anatase-type, has a particle size of 20-50 nm, and a specific surface area of ​​more than 50 m2 / g.

5. The modified polystyrene plastic material according to claim 1, characterized in that: The phosphorus-containing benzoxazine prepolymer is prepared by reacting bisphenol A, paraformaldehyde and p-aminophenyl diphenyl phosphate in a molar ratio of 1:2:1 in a toluene solvent with p-toluenesulfonic acid as a catalyst at 110-120° C. for 6-8 hours under nitrogen protection.

6. The modified polystyrene plastic material according to claim 1, characterized in that: The graphene quantum dots are prepared by mixing graphite powder and potassium nitrate in a mass ratio of 1:5 in concentrated sulfuric acid in an ice bath, reacting at 180-200° C. for 12-18 hours, and then diluting, centrifuging, dialysis, and freeze-drying.

7. The modified polystyrene plastic material according to claim 1, characterized in that: The hyperbranched polyamide ester is prepared by using trimethylolpropane, trimellitic anhydride and octadecylamine as raw materials in a molar ratio of 1:3:2, and reacting at 180-200° C. for 4-6 hours under nitrogen protection.

8. A method for preparing the modified polystyrene plastic material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polystyrene plastic is pre-treated by combining physical screening and chemical cleaning to remove impurities and crush into particles with a size of less than 2 mm; Preparation of phosphorus-containing benzoxazine prepolymer, graphene quantum dots, hyperbranched polyamide ester, rare earth complex and organic montmorillonite; Weigh hydrogenated SBS, PET-PBS copolymer, nano titanium dioxide, antioxidant 1010, calcium stearate, prepared phosphorus-containing benzoxazine prepolymer, graphene quantum dots, hyperbranched polyamide ester, rare earth complex according to the ratio. , organic montmorillonite; Add the pretreated polystyrene plastic particles and the above components into a high-speed mixer in sequence, and stir at a speed of 800-1200 r / min for 10-15 minutes to fully mix them; The mixed materials are added into a twin-screw extruder, the extruder temperature is set to 180-190°C in the first section, 190-200°C in the second section, 200-220°C in the third section, the screw speed is 200-300r / min, and the melt-blending extrusion, cooling, air-drying, pelletizing, homogenization and packaging are performed.

9. The preparation method according to claim 8, characterized in that: The preparation method of the organic montmorillonite comprises the following steps: adding sodium montmorillonite to deionized water to prepare a suspension with a mass fraction of 5-10%, dispersing the suspension for 30-60 minutes under high-speed stirring, then adding hexadecyltrimethylammonium bromide with a mass ratio of 1:2-1:3 to montmorillonite, and continuing stirring for 4-6 hours. After the reaction is completed, centrifuging the suspension, washing the obtained solid with deionized water until there is no bromide ion in the washing liquid, and finally drying the washed solid at 80-100° C. for 12-18 hours, and grinding the washed solid to obtain the organic montmorillonite.

10. The preparation method according to claim 8, characterized in that: The rare earth complex The preparation method is: europium nitrate Dissolve in anhydrous ethanol to prepare a solution A with a concentration of 0.1-0.5 mol / L, dissolve o-phenanthroline in anhydrous ethanol to prepare a solution B with a concentration of 0.2-0.6 mol / L, and dissolve terephthalic acid in anhydrous ethanol to prepare a solution C with a concentration of 0.15-0.4 mol / L; slowly drop solution B and solution C into solution A under stirring, control the dropping speed, make the reaction proceed at room temperature, and the dropping process lasts for about 30-60 minutes; after the dropping is completed, heat the reaction system to 60-80°C, continue to stir and react for 4-8 hours; after the reaction is completed, cool the reaction mixture to room temperature, and then filter or centrifuge the reaction product to obtain a precipitate, wash the precipitate with anhydrous ethanol for multiple times, and finally dry it in a vacuum oven at 60-80°C for 12-24 hours to obtain a rare earth complex. .

Citation Information

Patent Citations

  • In-situ fiber-forming toughened regenerated polystyrene material and preparation method

    CN102702633A

  • Method for recycling polystyrene shell materials of waste electrical appliances

    CN102719030A

  • Novel modified extruded polystyrene board

    CN106738988A

  • Recycling method for polystyrene plastic in shells of waste electronic products, and polystyrene composite material and application thereof

    CN108641206A

  • Method for preparing regenerated plastic from waste plastic

    CN113416362A

Cited By

  • High-peel-strength biaxially oriented nylon film

    CN120682627A